Study on axial compressive properties of RC square columns strengthened with prestressed CFRP sheets. (October 2020) - Lu, Chun-Ling; Xiao, Yi-Peng; Wang, Qiang; Zhu, Wan-Xu
Highlights: The performance of 10 prestressed CFRP reinforced concrete columns was tested. Different prestressed CFRP wrapping methods on the axial compression were observed. The mechanism by which CFRP actively restrains the reinforced columns was analyzed. The reinforced components axial bearing capacity was studied theoretically. Abstract: Carbon-fiber reinforced polymer (CFRP) has the advantages of high strength, high elasticity, light weight, corrosion resistance, high fatigue resistance, and ease of construction and has become the main seismic strengthening strategy for civil engineering structures. This paper presents a new technique to quickly strengthen reinforced concrete square columns using prestressed CFRP. The axial compression performance of three groups of 10 prestressed CFRP reinforced concrete square columns was tested. By observing the effects of different prestressed CFRP wrapping methods and the range and degree of prestressing on the axial compression, it was possible to analyze the mechanism by which CFRP actively restrains the reinforced columns. Changes in the ductility of the reinforced components were examined and their axial bearing capacity was studied theoretically. The test results and analytical studies show that, the larger the degree of prestressing and range of wrapping, the stronger the lateral deformation constraint placed on the core concrete, and the greater the bearing capacity and ductility. The increase in bearing capacity can reach 65.91%. Increasing the degree of prestressing of the CFRP is also more effective than increasing its reinforcement range. The axial bearing capacity of the reinforced columns was also calculated theoretically by establishing strength calculation models for the confined concrete for different methods and ranges of reinforcement. The predicted results were in good agreement with the test results, so, the models can provide a firm theoretical basis for practical applications.